ANALISIS PENGARUH BRAND IMAGE, PERCEIVED PRICE, DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTIONS PADA PRODUK PRIVATE LABEL - Maria Rosari Sikteubun; I Made Bayu Dirgantara; Rista Nurdianasari (Diponegoro Journal of Management, 2022)
Creating buying interest in consumers is one important thing that needs to be done. Not only that, manufacturers also need to ensure that consumers feel satisfied when using the products that have been purchased. It is important for manufacturers to be able to ensure that consumers can always remember their products and prevent consumers from switching to other brands (Yee & Shaheen, 2016). Based on previous research by Lien et al. (2015), Phing-Li (2017), Liu, et al. (2021), Ayub (2021) and Yuan et al., (2020), researchers will conduct research that aims to be able to find out whether Brand Image, Perceived Price and Perceive Value have an influence on Purchase Intentions on private label products with case studies, namely: private label Lotte Wholesale. This research was conducted with the intention of knowing more deeply whether the factors in the two different studies when combined will get more detailed results so that they can find out which factors can influence buying interest from a brand. The results of this study, which took 153 respondents and processed using Multiple Linear Regression Analysis, showed that the Brand Image Variable had a negative and significant influence on Purchase Intentions, while the Perceived Price Variable and Perceived Value Variable had a positive and significant influence on Purchase Intentions. The results of this study can be used as material to increase knowledge and insight about Purchase Intentions for companies, so that the management of the Lotte Wholesale Semarang supermarket company can design a mechanism for implementing the company's continuation properly.